Adherence to Endoscopy Biopsy Guidelines for Celiac Disease. Issue 4 (October 2015) - Ofei, Sylvia; Boyle, Brendan; Ediger, Tracy; Hill, Ivor
ABSTRACT: Objective: Histologic changes in celiac disease (CD) may be patchy or confined to the bulb. Present guidelines recommend obtaining multiple biopsies from the bulb and distal duodenum when evaluating for CD. Adherence to these recommendations among adult gastroenterologists is low. There are no such data for pediatric gastroenterologists. This study compared endoscopic biopsy practices among pediatric gastroenterologists in histologically confirmed patients with CD to those without histologically confirmed CD. Methods: Retrospective review of esophagogastroduodenoscopies (EGDs) during a 13-month period was performed. Children with histologically confirmed CD and a random sample of age-matched children without CD were identified. Endoscopy and histology reports were reviewed. The site and number of biopsy samples obtained was recorded. The groups were compared for number of biopsies. Results: A total of 98 children with CD were compared with 103 controls without CD. The number of biopsies obtained in the group with CD was higher than the group without CD (5.9 ± 1.6 vs 3.6 ± 1.2) ( P  < 0.0001). In children with CD, 80.5% had ≥5 biopsies compared with 11.7% in the group without CD ( P  < 0.0001). Only 10% of the children in the group with CD had bulb biopsies documented compared with none in the group without CD. Conclusions: Pediatric gastroenterologists at our center generally obtain the recommended number of biopsies in children with histologically confirmed CD but seldom document biopsies from the bulb. In those without histologic evidence of CD, fewer biopsies are obtained with none documented from the bulb. Failure to take the recommended number of biopsies could result in some missed cases of CD.